Characterization of BoHV-4 ORF45 - Russo, Luca; Capra, Emanuele; Franceschi, Valentina; Cavazzini, Davide; Sala, Roberto; Lazzari, Barbara; Cavirani, Sandro; Donofrio, Gaetano (Frontiers in Microbiology, 2023)
Bovine herpesvirus 4 (BoHV-4) is a Gammaherpesvirus belonging to the Rhadinovirus genus. BoHV-4 natural host is the bovine, and the African Buffalo is BoHV-4 natural reservoir. Anyhow, BoHV-4 infection is not associated to a specific disease. Genome structure and genes are well conserved in Gammaherpesvirus, and orf45 gene and its product, ORF45, is one of those. BoHV-4 ORF45 has been suggested to be a tegument protein, however, BoHV-4 ORF45 structure and function have not yet been experimentally characterized. In the present study, it is shown that BoHV-4 ORF45, despite its poor homology with other characterized Rhadinovirus ORF45s, is structurally related to Kaposi’s sarcoma-associated herpesvirus (KSHV), is a phosphoprotein and localizes in the host cell nuclei. Through the generation of an ORF45-null mutant BoHV-4 and its pararevertant, it was possible to demonstrate that ORF45 is essential for BoHV-4 lytic replication and is associated to the viral particles, as for the other characterized Rhadinovirus ORF45s. Finally, the impact of BoHV-4 ORF45 on cellular transcriptome was investigated, an aspect poorly explored or not at all for other Gammaherpesvirus. Many cellular transcriptional pathways were found to be altered, mainly those involving p90 ribosomal S6 kinase (RSK) and signal-regulated kinase (ERK) complex (RSK/ERK). It was concluded that BoHV-4 ORF45 has similar characteristics of those of KSHV ORF45 and its unique and incisive impact on cell transcriptome paves the way to further investigations.